Research on Railway Emergency Rescue Path Selection Based on GIS. (November 2019) - Tang, Zhaoping; Zhou, Shengyu; Geng, Biao; Sun, Jianping
Abstract: After the railway emergency, how to transport emergency rescue resources to the accident site in time and reduce all kinds of unnecessary losses caused by the accident is the primary purpose. Based on the theory of Geographic Information System (GIS), a calculation model of the shortest path was established. By using ArcMap software, the network data set based on railway network was analyzed and calculated, and the shortest path from emergency rescue point to accident point was solved and visualized. And supposed that an emergency happened in the area under the jurisdiction of Nanchang Railway Administration, and made an empirical analysis of it. It provides reference for the selection of emergency rescue path after railway emergencies.